2012
DOI: 10.1186/1472-6963-12-445
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and cost of a new model of care for managing acute knee injuries: the Calgary acute knee injury clinic

Abstract: BackgroundMusculoskeletal disorders (MSDs) affect a large proportion of the Canadian population and present a huge problem that continues to strain primary healthcare resources. Currently, the Canadian healthcare system depicts a clinical care pathway for MSDs that is inefficient and ineffective. Therefore, a new inter-disciplinary team-based model of care for managing acute knee injuries was developed in Calgary, Alberta, Canada: the Calgary Acute Knee Injury Clinic (C-AKIC). The goal of this paper is to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Given that the average cost of a knee MRI in Alberta is $540 [27], ordering fewer MRIs by having patients with acute knee injuries assessed in a clinic like the AKIC could achieve a cost-saving of $86,400 per 1000 patients with knee injuries. These results support those of a previous study by Lau et al which showed that AKIC patients had lower MRI utilization rates and made less visits to their primary care physician, to the emergency department, as well as to specialists, thus resulting in a 63% decrease in overall patient care costs [25].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Given that the average cost of a knee MRI in Alberta is $540 [27], ordering fewer MRIs by having patients with acute knee injuries assessed in a clinic like the AKIC could achieve a cost-saving of $86,400 per 1000 patients with knee injuries. These results support those of a previous study by Lau et al which showed that AKIC patients had lower MRI utilization rates and made less visits to their primary care physician, to the emergency department, as well as to specialists, thus resulting in a 63% decrease in overall patient care costs [25].…”
Section: Discussionsupporting
confidence: 94%
“…More general clinicians are relying on advanced imaging to provide a diagnosis, thus driving uncontrolled costs and a non-sustainable system of care. The AKIC model of utilizing NPEs is a viable, timely, and cost-effective alternative to the current practice [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knee disorders are a common reason for seeking diagnosis and management in primary care and can significantly impact quality of life of individuals [ 1 – 3 ]. However, evidence shows the limited ability of medical providers to perform an appropriate physical examination to make a diagnosis [ 4 , 5 ]. This has led to an overreliance on imaging or inappropriate referral to specialists to confirm a diagnosis, which incurs increasing health care costs and unnecessary delays to initiate conservative care [ 4 – 8 ].…”
Section: Introductionmentioning
confidence: 99%